The Role of Social Media (Youtube) in Increasing Interest in Religious Learning Among FAI Students in Private Universities - Sono, Devita Sari; Rahmatullah, Azam Syukur; Jubba, Hasse; Aziz, Akbar Nur (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Several challenges are faced in religious learning, such as low student motivation and high academic load. As one of the most popular digital platforms, YouTube has great potential as an innovative and interactive learning tool. This study aims to analyze the role of the YouTube social media platform in increasing interest in religious learning. This study uses a qualitative approach with a survey method to collect data from 33 FAI students at the University of Muhammadiyah Yogyakarta. The study results show that YouTube can be a practical learning resource, increase student involvement in the learning process, and increase their understanding of religious materials.